Event‐triggered adaptive tracking control for nonlinear systems with predefined time‐varying output constraints based on Nussbaum design. (16th July 2021) - Zhang, Jiaming; Niu, Ben; Duan, Peiyong; Zhao, Ping; Wang, Huanqing
Abstract: In this article, an event‐triggered adaptive tracking control scheme is proposed for uncertain nonlinear systems with the predefined time‐varying output constraint requirements by using barrier Lyapunov function (BLF) method. One of the significant novelties in the proposed design procedure is that the event‐triggered control strategy is first designed jointly with nonlinear systems under the predefined time‐varying output constraint requirements, such that the communication resources are effectively saved. Then, we set a time in advance to make the systems begin obeying the constraint requirements before running the time by using a shifting function nested in the first BLF. Meanwhile, the requirement (the initial value of the coordinate transformation needs to be in the constraints) is released by using the shifting function. For the unknown control gains in the considered system, a Nussbaum design procedure is employed to eliminate the effects of the unknown control gains. In addition, it is proved that all signals in the whole closed‐loop system are bounded and the output constraint requirements are not violated. In the end, the simulation results illustrate the validity of the proposed scheme through a practical example.